1998
DOI: 10.2202/1558-9544.1056
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Selection in Health Insurance

Abstract: Individual choice among health insurance policies may result in risk-based sorting across plans. Such adverse selection induces three types of losses: efficiency losses from individuals' being allocated to the wrong plans; risk-sharing losses, because premium variability is increased; and losses from insurers' distorting their policies to improve their mix of insureds. We discuss the potential for these losses and present empirical evidence on adverse selection in two groups of employees: Harvard University an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
143
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 5 publications
1
143
0
2
Order By: Relevance
“…And it should be acknowledged that several recent studies have failed to find evidence of adverse selection in insurance. While adverse selection has been found where insurance companies are prohibited from using their knowledge of individual risk to set individual prices, such as in multi-plan group insurance (Cutler and Zeckhauser 1997), in the absence of this prohibition we often fail to observe the positive correlation between risk levels and insurance quantities predicted by simple adverse selection models. While such predicted correlations have been observed in markets for annuities (Finkelstein and Poterba 2002), recent studies have failed to find them in individual life insurance (Cawley and Philipson 1999) auto insurance (Chiappori andSalanie 2000, Hemenway 1990), and medical insurance (Cardon andHendel 2001, Browne andDoerpinghaus 1993).…”
Section: Introductionmentioning
confidence: 83%
“…And it should be acknowledged that several recent studies have failed to find evidence of adverse selection in insurance. While adverse selection has been found where insurance companies are prohibited from using their knowledge of individual risk to set individual prices, such as in multi-plan group insurance (Cutler and Zeckhauser 1997), in the absence of this prohibition we often fail to observe the positive correlation between risk levels and insurance quantities predicted by simple adverse selection models. While such predicted correlations have been observed in markets for annuities (Finkelstein and Poterba 2002), recent studies have failed to find them in individual life insurance (Cawley and Philipson 1999) auto insurance (Chiappori andSalanie 2000, Hemenway 1990), and medical insurance (Cardon andHendel 2001, Browne andDoerpinghaus 1993).…”
Section: Introductionmentioning
confidence: 83%
“…Unlike the Medicare risk selection studies that are national in scope, most studies of risk selection in the employer-sponsored health insurance market examine single employers or employer coalitions, and the available evidence is mixed. Cutler and Zeckhauser (1998) found substantial favorable risk selection among state government employees in Massachusetts for the HMO plan relative to the fee-for-service plan. Altman, Cutler, and Zeckhauser (2003), examining the same data set, find that almost half of the expenditure difference between indemnity and HMO plans for eight medical conditions is due to a lower incidence rate among HMO patients (favorable risk selection), with the remaining difference due to lower provider reimbursement.…”
Section: Introductionmentioning
confidence: 97%
“…Health insurance companies often have incentives to design their plans to attract low-risk enrollees and repel high-risk enrollees. It has been argued that a health insurance market providing both managed care and non-managed care plans may be inefficient because managed care plans may be more likely to implement such strategies, resulting in too few people in non-managed care plans (Cutler and Zeckhauser, 1998). In fact, a number of studies have shown that Medicare HMOs attract a disproportionate share of the healthy elderly population (Eggers, 1980;Eggers and Prihoda, 1982;Brown et al, 1993;Cox and Hogan, 1997;Call et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This premium, in turn, may drive more low-risk enrollees away, requiring a recalculation of the differential to a higher level, and potentially resulting in what has come to be known as a ''death spiral'' (cf. Price and Mays 1985;Buchmueller and Feldstein 1997;Buchmueller and DiNardo 2002;Cutler and Zeckhauser 1998). Even if an (interior) equilibrium is reached, it will be one where enrollment in generous plans will be lower than it would have been had differential premiums been risk-adjusted in some fashion.…”
Section: Death Spiral or Euthanasia? The Demise Of Generous Group Heamentioning
confidence: 99%